Kritik terhadap Praktik Asesmen Formatif di Sekolah Dasar: Implementasi, Kendala, dan Solusi Penguatan - Hukom, Julham (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This study aims to critique formative assessment practices in elementary schools by examining their implementation, obstacles, and relevant strengthening solutions to improve learning effectiveness. Using a critical review approach to empirical research and literature from the past five years, this study found that formative assessment at the elementary school level has been implemented, but it has not fully aligned with the principles of continuous assessment that provide meaningful feedback to students. Teachers tend to use formative assessment as a one-time measurement tool, rather than as a reflective process integrated with learning. The main obstacles identified include limited teacher assessment competencies, high workloads, inconsistent feedback quality, and minimal institutional support for developing a culture of reflection. This study recommends strengthening through increasing assessment literacy, optimizing supporting technology, developing professional communities of practice, and establishing school policies that emphasize the importance of formative assessment as part of authentic learning. These findings underscore the urgency of repositioning formative assessment as a primary pedagogical strategy to encourage student engagement and holistic development.